Strategi Pemasaran Produk SimPel iB Bank BTN Syariah Saat Pandemi Covid-19 - Fayumi, Ahmad; Ryan Isnandar, Fajri (LPPM Universitas Islam 45, 2023)
This research focuses on the marketing strategy of the iB Student Savings BTN (SimPel) product during the Covid-19 at Bank BTN KCPS Cikarang. Researchers conducted data analysis methods using a mix of methods, namely qualitative and quantitative methods with an IFE matrix approach, an EFE matrix,and a SWOT matrix. By using the depth interview (in-depth interviews) to several human resources who have the authority to determine strategic decisions related to the marketing of the iB Student Savings BTN product. The results showed that based on the SWOT matrix, the SO strategy was obtained which focused on its target market and utilized various digital media in terms of introducing and marketing SIMPEL iB products. The WO strategy is to collaborate with various non-academic educational institutions and. ST strategy is to take advantage of the company's internal strengths to seize opportunities in the form of submitting offers of cooperation to schools using email and conducting online meetings